English Translation of Semantic Features of “Fictional Orality” in Tales of my Aunt Panchita - Vargas Castro, Ericka (2024)
This paper is part of the research project «Fictional orality» in the translation of short stories by Carmen Lyra, registered at the Institute of Linguistic Research of the University of Costa Rica under the number 745-C1-002. It analyzes the Spanish to English translation of components with a semantic function as part of the features of «fictional orality» in Tales from my Aunt Panchita by the Costa Rican writer Carmen Lyra. In particular, the colloquial lexicon, and the semantic relations of similarity are traced. To do so, first, we systematized the results related to translation techniques, methods, and norms; afterwards, we contrasted them with the tendencies identified for the pragmatic field and for phraseological units, according to previous research part of this project; and, finally, we discussed the most representative examples of semantic or stylistic divergence between the source text and its English counterpart.